2009
DOI: 10.1590/s0034-89102009000100018
|View full text |Cite
|
Sign up to set email alerts
|

Use of analgesics in adults with pain complaints: prevalence and associated factors, Turkey

Abstract: OBJECTIVE:Use of analgesics has been increasingly recognized as a major public health issue with important consequences in Turkey. The objective of the study was to determine the prevalence and patterns of analgesics usage and associated factors in adults with pain complaints. METHODS:A cross-sectional study was conducted in 15 cities selected from fi ve demographic regions in Turkey. The study sample population comprised 1.909 adults 18-65 age groups suffering from pain. The sampling method was multi-step str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
5
12
0
Order By: Relevance
“…[10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population. Studies conducted in Taif, Sweden, United States, and Norway have shown an association between age and analgesic use.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…[10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population. Studies conducted in Taif, Sweden, United States, and Norway have shown an association between age and analgesic use.…”
Section: Discussionsupporting
confidence: 80%
“…Analgesics are the most frequently consumed products in treatment groups. [1] According to the SFDA, the following analgesics are available as OTC on the Saudi market: Paracetamol, aspirin, ibuprofen, naproxen, and diclofenac. [3] Paracetamol, acetaminophen or acetyl-para-aminophenol, is used primarily as a non-opioid analgesic and antipyretic medication.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Use of medicines was reported by 73% of respondents who mentioned pain in fi ve Turkish cities. 16 In a study performed in Norway, 54% of respondents reported consuming analgesics in the 14 days prior to the interview. 8 In the United States, the percentage of individuals who use analgesics reach 76%.…”
Section: Discussionmentioning
confidence: 99%